Consolidation of State Authorities, Society and Individuals on Drug Prevention - Nazelskis, Eugenijus (Acta Paedagogica Vilnensia, 2004)
The aim of this article is to show the necessity of integrated efforts of the state, society and a person in order to overcome the increase of drug using in the country, especially among young people. So on the basis of numbers and facts, the analysis of the present situation has been done. The investigation shows that drug using is increasing rapidly and attempts to stabilize it have failed. On the basis of this situation an author draws the presumption which could be the background for prevention and stabilization of the situation in the country. In the author’s opinion this presumption could become a part of strategic goals of the state policy in overcoming the drug using. Five presumptions have been excluded. All of them are related to the necessity to change the outlook of the state, society and a person towards drug using and its distribution. In the article a lot of attention is devoted to the role of society in the process of stabilization of drug using. On the basis of empiric data obstacles and barriers for successful prevention and arousing threat are shown. Critical opinion on the activities of the government and other institutions is given concerning the process of overcoming drug using. Reasons are given for the facts that efforts to overcome drug using by different institutions are not coordinated and have a lot of shortcomings as well as lack of scientific background. In the article principles are presented which could serve as a basis for prevention strategy of drug using and state policy in stabilization and overcoming drug using. There are six principles: 1. Development of intolerance against illegal drug distribution and drug using in general; 2. Support of antidrug tendencies (necessity to increase antidrug propaganda and support for those who dare speak against drug using); 3. Tolerance and respect for those who try to refuse drug using (patients); 4. Different ways of treatment and implementation of new methods in drug treatment; 5. Recognition and development of individual’s rights and duties (meaning that in the process of prevention not only rights of drug user but also duties should be recognised); 6. Principle of applying (which could be applied to people avoiding treatment). In the author’s opinion the application of all principles mentioned above could ensure long-term complex prevention work. The article is written using theoretical and empirical methods of investigation: a) analysis of scientific resources, international and national legislation; b) questionary answers by drug users; c) information from interviewing drug users and their relatives, synthesis data evolution.